Design of bio-based supramolecular structures through self-assembly of α-lactalbumin and lysozyme - F. Xavier Malcata (2016)
Bovine alpha-lactalbumin (alpha-La) and lysozyme (Lys), two globular proteins with highly homologous tertiary structures and opposite isoelectric points, were used to produce bio-based supramolecular structures under various pH values (3, 7 and 11), temperatures (25, 50 and 75 degrees C) and times (15, 25 and 35 min) of heating. Isothermal titration calorimetry experiments showed protein interactions and demonstrated that structures were obtained from the mixture of alpha-La/Lys in molar ratio of 0.546. Structures were characterized in terms of morphology by transmission electron microscopy (TEM) and dynamic light scattering (DLS), conformational structure by circular dichroism and intrinsic fluorescence spectroscopy and stability by DLS. Results have shown that protein conformational structure and intermolecular interactions are controlled by the physicochemical conditions applied. The increase of heating temperature led to a significant decrease in size and polydispersity (PDI) of alpha-LaeLys supramolecular structures, while the increase of heating time, particularly at temperatures above 50 degrees C, promoted a significant increase in size and PDI. At pH 7 supramolecular structures were obtained at microscale e confirmed by optical microscopy e displaying also a high PDI (i.e. > 0.4). The minimum size and PDI (61 +/- 2.3 nm and 0.14 +/- 0.03, respectively) were produced at pH 11 for a heating treatment of 75 degrees C for 15 min, thus suggesting that these conditions could be considered as critical for supramolecular structure formation. Its size and morphology were confirmed by TEM showing a well-defined spherical form. Structures at these conditions showed to be stable at least for 30 or 90 days, when stored at 25 or 4 degrees C, respectively. Hence, alpha-LaeLys supramolecular structures showed properties that indicate that they are a promising delivery system for food and pharmaceutical applications.